Synthesis and properties of photocatalysts for the high degradation of sulfadiazine - Pei, Zhenzhao; Li, Feng (European Journal of Chemistry, 2021)
In this study, it was discovered for the first time that the BiOBr/Bi3.84W0.16O6.24 catalyst can efficiently degrade sulfadiazine (SDZ). Multiple techniques, such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV-Vis diffuse reflection spectroscopy (DRS) were applied to research the structures, morphology and photocatalytic properties of as-prepared samples. In addition, the effect of different synthesis pH environment and initial SDZ solution pH on the catalyst degradation efficiency were discussed. The BiOBr/Bi3.84W0.16O6.24 catalyst synthesized under the condition of pH = 7 exhibited excellent photocatalytic activity for photodegradation of SDZ of 91% within 120 min under simulated solar light irradiation. Also, the roles of the radical species have been studied, and the ·O2- and h+ were proved to dominate the photocatalytic process. Based on the experimental results, the photocatalytic mechanism was proposed.